The Piousness from The Suspiciousness is the Secret of Innovation in Halal Industry; "Study in Light of Malaysian and International Islamic Fiqh Academy OIC Standards. - Ahmed Salem Ahmed Alejili (Al-Arfa: Journal of Sharia, Islamic Economics and Law, 2025)
Due to the fundamental difference between the nature of the Halal system and the existing traditional systems related to services and products, legislative and research efforts attempt to harmonize the criteria for resolving the prevailing standards by employing the facilitation and mitigation licenses capacity in the Islāmic law, which directly affects the legitimate content of the Halal and its stability and independence within these criteria ,which led the researcher to highlight this problem in light of halal legalization manner in International Islāmic Fiqh Academy standards and Malaysian standards. by evaluating of both of standards especially in the transformation IstihÉlah and Automated slaughtering, by comparing between the manner that has chosen from each of those standards the researcher has found the Islāmic Fiqh Academy has legalized that matters but the Malaysian standards have chosen to be far away from the disagreement points between the Islāmic schools, which led, in the end, to push the research to create the alternative elements instead of continuing the argument to support that points by Islāmic justifications the option that chosen by the Islāmic fiqh academy, which has shown the effects of the piousness from the suspiciousness and its inspired to support the innovation in halal industry and to protect the halal essence without a need for any justifications.